Ventsel E.S., Shchukin A.V., Skapovich V.I. On the interrelation of life and wear of the blade when carrying out working operations. - Венцель, Е.С.; Щукин, А.В.; Щукин, А.В.; Скапович, В.И.; Скапович, В.И. (Problems of Tribology, 2014)
While examining earth-moving machines it was determined that the wear of the operating tools blades, particularly ones of the motor-graders, is most often characterized by the change in the size of the part in direction, perpendicular to the surface of friction. Hence, it has been assumed that the blade’s wear appears throughout the contact area uniformly, i.e. is of the linear character. .The empiric dependence, describing the wear process of the bulldozer blade wear is known, according to which the wear occurs linearly over the whole period of time of the blade’s operation in the abrasive environment, which does not take into account the dynamics of this process. Therefore, we have considered fuller characteristics of the blade wear process in terms of the dependence hиз = f(t), where hиз is part wear, t is part operating lifelength. Working load of the shovel of the moto-grader (therefore of its blades too) is presented with the use of normal law of frequency distribution. Mathematical expectation of the normal loads is stipulated for each working operation by the complex of reasons. As a result of the researches carried out, the dependencies of the total probability of the failure-free operation of the blade from the wear and dynamic compounds of the load to the shovel, as well as the dependencies of the blade life from the time of his operation in the abrasive environment on the 3 categories of coat have been received.